Uniform decoration of silver nanoparticle on exfoliated graphene oxide sheets and its ammonia gas detection. Issue 1 (January 2016) - Kavinkumar, T.; Manivannan, S.
Abstract: Silver nanoparticles (AgNP) decorated graphene oxide (GO) sheets were prepared by reducing AgNO3 with vitamin C in the presence of GO. Different molar concentration of AgNO3 played a significant role in the size of AgNP in GO. The synthesized AgNP–GO composites were characterized by powder X-ray diffraction, scanning electron microscopy, ultraviolet–visible–near infrared, Fourier transform infrared and micro Raman spectroscopy techniques. We demonstrated the fiber optic gas sensor using reduced graphene oxide (rGO) and AgNP–GO composites for 0–500 ppm ammonia vapor concentrations at 27 °C. Sensitivities of rGO, 0.1 M AgNP–GO and 0.6 M AgNP–GO composites coated fiber optic sensors were calculated as −0.08, −0.177, −0.12 counts/ppm respectively. The agglomeration of AgNP at 0.6 M concentration along with increased particle size significantly decreased the sensing performance.